2015
DOI: 10.1155/2015/623986
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Coronary Flow in an Experimental Slow Flow Model in Swines: Angiographic and Pathological Insights

Abstract: Objective. Pathomechanism of coronary slow flow phenomenon remains largely unclear now. Present study observed the pathological and angiographic evolution in a pig model of coronary slow flow. Methods. Coronary slow flow was induced by repeat coronary injection of small doses of 40 µm microspheres in 18 male domestic pigs and angiographic and pathological changes were determined at 3 hours, 7 days, and 28 days after microspheres injection. Results. Compared to control group treated with coronary saline injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Frangogiannis [80] classified the healing process of myocardial infarct into 3 distinct but overlapping phases: the inflammatory phase, the proliferative phase, and the maturation phase, while Nahrendorf et al [81] summarized the roles of monocytes/macrophages in infarct healing, including 1) release inflammatory mediators; 2) release proteases; 3) phagocytose apoptotic and necrotic myocytes and neutrophils and other debris; 4) promote angiogenesis; 5) transport reparative enzymes and prosurvival factors; and 6) stimulate collagen synthesis and deposition by myofibroblasts. It has been shown that multiple injections of microspheres also induce myocardial injuries similar to those seen in patients after revascularization [77]. Figure 8 shows the patchy microinfarct and infiltration of inflammatory cells in infarcted myocardium 3 days after microembolization.…”
Section: Histopathologymentioning
confidence: 74%
See 2 more Smart Citations
“…Frangogiannis [80] classified the healing process of myocardial infarct into 3 distinct but overlapping phases: the inflammatory phase, the proliferative phase, and the maturation phase, while Nahrendorf et al [81] summarized the roles of monocytes/macrophages in infarct healing, including 1) release inflammatory mediators; 2) release proteases; 3) phagocytose apoptotic and necrotic myocytes and neutrophils and other debris; 4) promote angiogenesis; 5) transport reparative enzymes and prosurvival factors; and 6) stimulate collagen synthesis and deposition by myofibroblasts. It has been shown that multiple injections of microspheres also induce myocardial injuries similar to those seen in patients after revascularization [77]. Figure 8 shows the patchy microinfarct and infiltration of inflammatory cells in infarcted myocardium 3 days after microembolization.…”
Section: Histopathologymentioning
confidence: 74%
“…The animals showed complete recoveries of flow reserve and LV ejection fraction, but LV dilation, 1 week later [66]. Bai et al [77] also reported a persistent LV dysfunction and progressive remodeling in swine model 28 days after repeated microsphere injection.…”
Section: Myocardial Perfusionmentioning
confidence: 87%
See 1 more Smart Citation
“…Our model is unique in inducing CME using autologous thrombus in the setting of preceding ischemia. The majority of the large animal studies of CME employed intracoronary injection of microspheres (4, 18, 2022). While the microspheres have some advantages (easy handling and dosing), they are chemically inert and therefore not chemoattractant.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary small-scale clinical studies confirmed that STDP could improve angina pectoris and attenuate vascular endothelial dysfunction in patients with slow coronary flow ( Wang et al, 2019 ; Lu et al, 2020 ; Tian et al, 2020 ), but the underlying mechanism is not fully unclear. In this study, we observed the angiographic effects of STDP in a large animal (Bama pig) with a slow-flow model established in our laboratory ( Hu et al, 2014 ; Bai et al, 2015 ) and observed its impact on serum and myocardial biomarkers related to inflammatory and angiogenetic pathways. We aimed to observe the effects of STDP by observing the coronary angiographic, hemodynamic, serum biomarkers, HE staining, and immunohistochemical staining changes in a swine model of coronary slow flow (SF) and explore the potential mechanisms related to these effects post-STDP treatment.…”
Section: Introductionmentioning
confidence: 99%